STUDIES ON MATURATION ,SPAWINING ,FECUNDITY AND SEX RATIO IN BARBUS (PUNTIUS) SARANA (HAMILTON-BUCHANAN ) FROM LAKE KOLLERU , ANDRA PRADESH. - MURTY, V. SRIRAMACHANDRA (Fishery Technology, 2017)
Barbus sarana contains only one batch of mature ova inthe mature ovaries to be spawned in one spawning act. Itspawns during July-September. The fecundity ranges from11,201 to 224,248 ova. There is a positive curvilinear correlationbetween total length and fecundity, the latter increasingwith length at a rate of less than cube of length. The stockof this species from lake KoUeru appears to be more fecundthan that inhabiting Loni reservoir. The sex ratio indicatesthat females outnumber males in all months and in largerlength groups. Females appear to reach a larger lengththan males.